Exome sequencing in genomic regions related to racing performance of Quarter Horses - Pereira, Guilherme L. [UNESP]; Malheiros, Jessica M. [UNESP]; Ospina, Alejandra M. T. [UNESP]; Chardulo, Luis Artur L. [UNESP]; Curi, Rogério A. [UNESP] (Springer Nature, 2019)
Among horses selected for speed, the racing line of Quarter Horses is characterized by high performance in sprint races, with these animals being considered the fastest horses in the world. However, few studies have investigated in more detail the polymorphisms and genes that act on this trait. The objective of this study was to analyze exomes and UTRs in regions previously associated with this trait by GWAS in Quarter Horse racehorses with contrasting maximum speed index (SImax), prospecting causal gene polymorphisms that are related to or are in strong linkage disequilibrium with racing performance. Genotypic and phenotypic records from 360 animals of the racing line of Quarter Horses, previously genotyped with an SNP chip to obtain individual genomic estimated breeding values for performance, were used for the formation and sequencing of two groups of animals with contrasting racing performance (20 animals with superior SImax and 20 with inferior SImax). Two rapid runs were performed using two pools of libraries containing 20 and 19 samples randomly chosen among the 40 samples with contrasting SIs. A total of 1203 variants (1105 SNPs and 93 InDels) were identified in 33 regions of interest obtained previously by GWAS. Twenty-nine of the polymorphisms (24 SNPs and 5 InDels) were considered to be important based on three different and independent approaches: SIFT scores classified as deleterious (< 0.05), degree of impact on the consensus region of each polymorphism, and different allele frequencies identified by Fisher’s exact test (p < 0.01) between the groups of horses with contrasting SImax. Thus, eight genes described as functional and positional candidates in previous studies (ABCG5, COL11A1, GEN1, SOCS3, MICAL1, SPTBN1, EPB41L3, and SHQ1) and nine new candidate genes (AKNA, ARMC2, FKBP15, LHX1, NOL10, TMEM192, ZFP37, FIG4, and HNRNPU), some of them with known function, were related to racing performance in Quarter Horses.
Keywords: Deletion; Insertion; Polymorphisms; SNP